My family : love and care, give and share - Bullard, Lisa.; Reibeling, Brandon (Minneapolis, Minn. : Picture Window Books, 2003)
A boy named Matthew describes the many parts of his family, including his divorced parents, stepmother and stepbrother, grandparents, adopted niece, and pets.
Includes bibliographical references (p. 24).
3.0
K-3.
K-3
Keywords: Families -- Juvenile fiction; Family life -- Fiction; Family life -- Fiction